(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Eight spontaneous habitats of Aronia melanocarpa is found in Western Ukraine. The ecological-phytocoenotic preferences of the species are analysed. An age stages identification key for A. melanocarpa is elaborated. The absolute number of individuals, density and age structure of two coenopopulations is studied. The degree of naturalizing, strategy, as well as current tendencies and limiting factors of distribution is revealed.